Collaborative teaching event explores Chinese New Year traditions - Ting, Hie-Ling (Corporate Communication Unit, UiTM Mukah Campus, 2025)
The event highlighted the history and customs of Chinese New Year, one of China’s most important festivals. The lecturer explained traditions like family reunions, red envelopes, fireworks, and festive foods. She also shared stories about how these practices bring luck and happiness. Comparisons were made with other global festivals to show what makes Chinese New Year unique. The lecturer used videos and photos to make the talk lively. Dr. Cheng stressed the value of cultural exchange. “Festivals like Chinese New Year teach us about family, hope, and sharing joy,” she said. Dr. Ting Hie Ling added, “This collaboration helped us see how traditions unite us all.”